2014
DOI: 10.3109/08039488.2014.972450
|View full text |Cite
|
Sign up to set email alerts
|

Association between ADH1C and ALDH2 polymorphisms and alcoholism in a Turkish sample

Abstract: These findings suggest that ADH1C*2 is associated with alcohol dependence in the Turkish population displaying a dominant inheritance model. ADH1C*2 allele may contribute to the variance in heritability of alcohol dependence. The ALDH2 -504Lys/Lys or Glu/Lys genotypes were not present in alcohol-dependent patients, similar to that seen in European populations and in contrast to the findings in the Asian populations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 36 publications
0
2
0
1
Order By: Relevance
“…The ALDH2 Glu504lys polymorphism is tied closely to occurrence and development of ALD in related individuals, 29 though its polymorphism does not contribute to alcohol dependence in the Turkish population. 30 Regardless of homozygous AA or heterozygous GA status, both guarantee elevated ACH level after alcohol drinking. A single-center study from the Fifth Medical Centre of the General Hospital of the Chinese People's Liberation Army reported that only 2.3% of ALD patients have the ALDH2*2 allele, compared with14.5% of the proportion of healthy controls (281 and 535 controls; odds ratio [OR] of 0.13 and 95% confidence interval [CI] of 0.07-0.24).…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
See 1 more Smart Citation
“…The ALDH2 Glu504lys polymorphism is tied closely to occurrence and development of ALD in related individuals, 29 though its polymorphism does not contribute to alcohol dependence in the Turkish population. 30 Regardless of homozygous AA or heterozygous GA status, both guarantee elevated ACH level after alcohol drinking. A single-center study from the Fifth Medical Centre of the General Hospital of the Chinese People's Liberation Army reported that only 2.3% of ALD patients have the ALDH2*2 allele, compared with14.5% of the proportion of healthy controls (281 and 535 controls; odds ratio [OR] of 0.13 and 95% confidence interval [CI] of 0.07-0.24).…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…In addition, weakened autophagy is involved and compromised lysosomal activity will lead to abnormal stacking of ethanol or acetaldehyde by-product including protein or DNA adducts. Guo et al 38 reported that observations both in vivo and in vitro are in favor of a beneficial role of ALDH2 in alcohol intake-facilitated fatty liver and inflammation through autophagy regulation (Table 1 16,[30][31][32][33][34][35][36][37] ).…”
Section: Alcoholic Liver Diseasementioning
confidence: 99%
“…Ayrıca protein kinaz-C, adenilsiklaz, alkol dehidrogenaz, aldehit dehidrogenaz gibi alkol metabolizmasında ya da metabolizma sonrasındaki çeşitli kimyasal basamaklarda görev alan enzimleri kodlayan genler, ödül mekanizması içinde yer alan opioid reseptör genleri araştırılmaktadır (Foroud ve ark. 1999, Ayhan ve ark. 2014, Gürel ve ark.…”
Section: Introductionunclassified